2015
DOI: 10.1016/j.ejmech.2014.10.065
|View full text |Cite
|
Sign up to set email alerts
|

A review on recent developments of indole-containing antiviral agents

Abstract: Indole represents one of the most important privileged scaffolds in drug discovery. Indole derivatives have the unique property of mimicking the structure of peptides and to bind reversibly to enzymes, which provide tremendous opportunities to discover novel drugs with different modes of action. There are seven indole-containing commercial drugs in the Top-200 Best Selling Drugs by US Retail Sales in 2012. There are also an amazing number of approved indole-containing drugs in the market as well as compounds c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
215
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 705 publications
(228 citation statements)
references
References 124 publications
0
215
0
Order By: Relevance
“…Amidst them, heterocycles with polycyclic ring system possess distinct rigid geometry displaying high functional specialization by orienting its substituents in three dimensional spaces, there by attracting great interest [2]. Indole is a bicyclic heterocyclic scaffold that find applications in medical therapy due to a variety of valuable biologic activities such as antiviral [3,4], antiinflammatory [5,6], anti-hyperlipidemic, antihypoglycemic, anti-hypertensive, anti-asthmatic, anti HIV [7], antidepressant [8] and notably anticancer [9][10][11][12][13][14][15] activity. Few marketed anticancer indole derivatives are vincristine, vinblastine, vinorelbine, vindesine, mitraphylline, cediranib and apaziquone [2].…”
Section: Introductionmentioning
confidence: 99%
“…Amidst them, heterocycles with polycyclic ring system possess distinct rigid geometry displaying high functional specialization by orienting its substituents in three dimensional spaces, there by attracting great interest [2]. Indole is a bicyclic heterocyclic scaffold that find applications in medical therapy due to a variety of valuable biologic activities such as antiviral [3,4], antiinflammatory [5,6], anti-hyperlipidemic, antihypoglycemic, anti-hypertensive, anti-asthmatic, anti HIV [7], antidepressant [8] and notably anticancer [9][10][11][12][13][14][15] activity. Few marketed anticancer indole derivatives are vincristine, vinblastine, vinorelbine, vindesine, mitraphylline, cediranib and apaziquone [2].…”
Section: Introductionmentioning
confidence: 99%
“…From previous work in our laboratory, it was found that double Sonogashira coupling of related arenes with aryldialkynes worked well using Pd 2 (dba) 3 , CuI, PPh 3 in DMSO as solvent. 16 Thus, a model set of aryldialkynes 3a-c and alkyldialkynes 3d-i were prepared (See supporting information) and their regioselective Sonogashira coupling with 2 proceeded uneventfully to give the corresponding products 4a-i.…”
Section: Resultsmentioning
confidence: 98%
“…Recently, a number of indole-containing compounds have revealed remarkable pharmacological activity and their utility as therapeutic agents has attracted considerable attention from chemists 1,2 . Libraries based on the indole scaffold have been developed to address the need for novel drugs with increased potency 3,4 .…”
Section: Introductionmentioning
confidence: 99%